A simplified sliding‐mode control method for multi‐level transformerless DVR - Hasan Komurcugil (16388513) (2022)
Here, a finite-control-set sliding-mode control (FCS-SMC) method is proposed for single-phase three-level T-type inverter-based transformerless dynamic voltage restorers (TDVRs). The inherent advantages of SMC (fast dynamic response and high robustness) are combined with FCS concept to increase the effectiveness of the method in achieving the desired control objectives. First, the use of FCS eliminates the modulator requirement, which reduces the design complexity in the practical implementation. Second, an effective method based on charging/discharging conditions of DC capacitors is proposed for balancing capacitor voltages using relevant switching state rather than combining DC voltage error with the inductor current error through a suitable weighting factor in forming the cost function. Therefore, the weighting factor necessity in the control algorithm is eliminated. Finally, the steady-state error in the compensation voltage is eliminated by the proportional-resonant (PR) controller. The studied T-type inverter-based TDVR topology offers an alternative solution to the existing DVR topologies. Experimental results are carried out to demonstrate the effectiveness of the proposed FCS-SMC method in maintaining the load voltage at the desired level despite the voltage sags, swells, and distortions occurring in the grid voltage. Other Information Published in: IET Power Electronics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/pel2.12266